Grafting Experiment Between Different Plant Species: Jackfruit (Artocarpus heterophyllus) and Durian (Durio zibethinus) - Riska Nabila; Jufrin Pagune; Nurlaila; Diana; Sulhandayani; Sukma Amrina Rosyada (International Journal of Integrated Science and Technology, 2023)
Grafting is the combination of different plant parts so that they unite and experience growth and development as one new plant after the tissue can regenerate. This research carried out a grafting experiment between jackfruit (Artocarpus heterophyllus) and durian (Durio zibethinus), two different types of fruit belonging to the same taxon class, namely dicotyledon. Even though these two plants belong to the same class, significant genetic differences and different environmental factors are the main challenges in efforts to combine them through grafting. The research results showed that no development occurred in the grafted plants. The factors for failure of grafting are genetic differences, environmental factors, and techniques in plant grafting.